Comment on “Unlocking the therapeutic potential of microalgal astaxanthin a super antioxidant in oral cancer and associated ailments” - Antonyraj Matharasi Perianaika Anahas; Dhanraj Ganapathy (Oral Oncology Reports)
Oral cancer treatment potentially advances with the application of C-phycocyanin (C-PC), a powerful antioxidant produced by cyanobacteria. By triggering mechanisms that impair the metabolism of mitochondria and cause cancer cells to initiate apoptosis, this pigment demonstrates potent apoptotic-inducing potentials. Innovative application for C-PC includes integrating it with fibrous scaffolds for long-term release, stimulating tissue regeneration, and lowering inflammation and oxidative damage after surgery. Surgical implants with C-PC, such stents and sutures, provide focused therapy at the locations of oral cancer. In order to enhance the therapeutic uses of C-PC in oral cancer, further studies may investigate genetically modified microalgae. Validating these therapeutic effects and advancing cyanobacterial pigment-based drugs into clinical applications demand further studies.